Performance Incentives : Their Growing Impact on American K-12 Education - Springer, Matthew G. (Book collections on Project MUSE., 2009)
"Offers an analysis of the promise and controversy around teacher pay for performance. Identifies potential strengths and weaknesses of performance-driven compensation policies and addresses key conceptual and implementation issues that have dominated the debate surrounding teacher compensation as an avenue for school reform"--Provided by publisher.